Street Markets at the Crossroads of Consumption and Climate Change: A Comparative Study of Informal Urban Economies in Brazil and Africa - Mohamed Ibrahim Hassan Farag; Ana Elisabeth de Brito Alves (PT. Riset Press International, 2026)
This study examines the intersection of street markets, consumption practices, and climate change within informal urban economies in Brazil and African cities. Street markets play a crucial role in food provisioning, income generation, and social interaction in urban contexts, particularly for low- and middle-income households. However, they are increasingly vulnerable to climate change impacts, such as rising temperatures, flooding, and extreme weather events, which disrupt market operations, food supply chains, and consumption patterns. This comparative qualitative study explores how climate stress reshapes informal market dynamics, focusing on vendor adaptation strategies, consumer behavior, and the role of informal governance in mitigating climate-related disruptions. By analyzing the lived experiences of street vendors and consumers across selected cities in Brazil and Africa, the study reveals shared vulnerabilities and context-specific adaptation strategies. The findings highlight that street markets are not passive victims of climate stress but active sites of resilience, where vendors and consumers employ everyday practices and social networks to adapt. This research contributes to the broader understanding of urban resilience and climate adaptation in informal economies, offering insights for policymakers to support climate-sensitive, inclusive interventions in informal urban spaces.